Artificial Intelligence and Virtual Reality Applied to Teaching and Learning. - Solorzano Ortega, Cecibel; Cabrera Barba, Francisco; Campoverde Villalta, Ana (Conexiones UG, 2025)
This research explores how VR and AI allow learning experiences to be personalized, adapting to the individual needs and styles of each student. In addition, it is analyzed how these immersive environments facilitate the acquisition of knowledge and skills in a more effective and attractive way. Through a systematic review of the scientific literature, the benefits and challenges associated with the implementation of these technologies in the classroom are identified.The study highlights that AI can analyze student data, offering personalized support. VR provides immersive experiences that simulate real environments. Challenges such as the need for infrastructure, teacher training and content development are also recognized. Recommendations are proposed to maximize the impact of VR and AI in education. In conclusion, this article demonstrates the potential of VR and AI to revolutionize education, offering more personalized and effective experiences.
Keywords: Artificial intelligence; Virtual reality; Teaching-learning